Cimaria vargasi n. gen, n. sp. (Gastropoda: Pyramidellidae: Odostomiinae) from the Pacific Coast of Costa Rica, Central America - Høisæter, Tore (Zootaxa, 2012)
The Panamic biogeographic province has long been thought to harbour a rich pyramidellid fauna. In the compilation of Keen (1971) the family is second only to the Turridae in being the most speciose gastropod family in the region, and no less than 350 species are listed. However a number of these have later been recognized to be synonyms, and in the update of the compilation by Skoglund (2002) the number of pyramidellids was reduced to 258.